A Mixed Method Study: Defining the Core Learning Needs of Nurses Delivering Care to Children and Young People with Rheumatic Disease to Inform Paediatric Musculoskeletal Matters, a Free Online Educational Resource - Nicola Smith; Christine English; Barbara Davies; Ruth Wyllie; Helen E. Foster; Tim Rapley (MDPI AG, 2022)
Children and young people with rheumatic diseases and their families are often supported by nurses who may not have had specialist training in paediatric rheumatology. The purpose of our study was to establish the core learning needs of all nurses who may encounter these children and young people in their clinical practice and use this information to inform the content and format of Paediatric Musculoskeletal Matters Nursing (PMM-Nursing) Engagement with nurses working in different roles and with various levels of experience in musculoskeletal medicine informed these learning needs and PMM-Nursing content. Mixed methods ascertained learning needs under the following themes: (1) Need for increased awareness about rheumatic disease; (2) Impact of experience and nursing role; (3) Need for increased knowledge about rheumatic disease and management. In addition, our methods informed design components for an impactful learning and information resource. Representatives from stakeholder nursing groups, social sciences, and web development used this information to create a suitable framework for PMM-Nursing. The content of PMM-Nursing is now live and freely available.